2022
DOI: 10.3389/fmolb.2022.875424
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of nitro-benzylidene phenazine as dengue virus-2 NS2B-NS3 protease inhibitor

Abstract: According to the World Health Organisation (WHO), as of week 23 of 2022, there were more than 1,311 cases of dengue in Malaysia, with 13 deaths reported. Furthermore, there was an increase of 65.7% during the same period in 2021. Despite the increase in cumulative dengue incidence, there is no effective antiviral drug available for dengue treatment. This work aimed to evaluate several nitro-benzylidene phenazine compounds, especially those that contain 4-hydroxy-3,5-bis((2-(4-nitrophenyl)hydrazinylidene)-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is important to consider whether CEP is a pan-assay interference compound (PAINS), given its bioactivity in so many in vitro and in vivo models. In recent years, the PAINS hypothesis has been widely used in the early screening of new drugs ( Baell and Holloway, 2010 ; Pouliot and Jeanmart, 2016 ; Nelson et al, 2017 ; Adnan et al, 2022 ; Salin et al, 2022 ; Das et al, 2023 ). For example, curcumin has been classified as a typical PAINS compound due to its invalid metabolic panacea properties as its clinical studies have not provided strong evidence for a therapeutic effect ( Nelson et al, 2017 ).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider whether CEP is a pan-assay interference compound (PAINS), given its bioactivity in so many in vitro and in vivo models. In recent years, the PAINS hypothesis has been widely used in the early screening of new drugs ( Baell and Holloway, 2010 ; Pouliot and Jeanmart, 2016 ; Nelson et al, 2017 ; Adnan et al, 2022 ; Salin et al, 2022 ; Das et al, 2023 ). For example, curcumin has been classified as a typical PAINS compound due to its invalid metabolic panacea properties as its clinical studies have not provided strong evidence for a therapeutic effect ( Nelson et al, 2017 ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They designed, constructed, and fully disclosed a database for a PAINS filter (PAINS-Remover, http://cbligand.org/PAINS/ ) to remove PAINS from screening libraries and exclude them from bioassays ( Baell and Holloway, 2010 ). This PAINS filter has been widely recognized in the industry ( Baell and Holloway, 2010 ; Pouliot and Jeanmart, 2016 ; Adnan et al, 2022 ; Salin et al, 2022 ; Das et al, 2023 ). We have screened the possibility of CEP being a PAINS compound.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The only comparative research was observed in silico , where two nitro-benzylidene phenazine derivatives ( Fig. 1 A and B ) with pharmacophore hit of 52 %–55 %, demonstrated their stability in the primary binding pocket of NS2B-NS3 protease with MM-PBSA binding energies ranging from −22.53 to −17.01 kcal mol −1 , indicating probable binding in DENV2 NS2B-NS3 protease [ 21 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…1 Reported phenazine and imidazole motifs as anti-dengue inhibitors. (A) and (B) The nitro-benzylidene phenazine derivatives reported as potential inhibitors of DENV2 NS2B-NS3 ( in silico study) [ 21 ]. (C) Imidazole nucleoside derivatives reported as DENV2 NS2B-NS3 inhibitor [ 25 ].…”
Section: Introductionmentioning
confidence: 99%